Exploratory study of the effectiveness of nebulised saline in children with neurodisability. Issue 3 (18th March 2021) - Galaz Souza, Natalia; Bush, Andrew; Tan, Hui-Leng
Respiratory morbidity is an important cause of hospitalisation and death in children with neurodisability [1]. Such children may have impaired respiratory function and inefficient cough due to weak bulbar and respiratory musculature, increased upper airway collapsibility and low lung compliance [2, 3]. Nebulised hypertonic saline (HS), usually 3% or 7%, is used to manage and prevent respiratory exacerbations in conditions such as cystic fibrosis (CF) and non-CF bronchiectasis. In patients with CF and non-CF bronchiectasis, nebulised HS has been associated with better airway clearance and lung function [4–8]. The prescription of nebulised saline in children and young people with neurodisability was associated with improved respiratory outcomes and was favourably received by patients and their caregivers https://bit.ly/3mSyzag